AOC removal and accumulation of bacteria in experimental sand filters - Hijnen,, W.; Van Der Kooij, D. (Revue des sciences de l'eau / Journal of Water Science, 1992)
Using small sand filets under well defined laboratory conditions, filtration experiments were performed with tap water supplemented with acetate. The objective of these experiments was to determine the effect of different acetate concentrations on (i) the removal of easily assimilable organic carbon (AOC) in the filter (ii), the clogging of the tiller and (iii) the bacteriological quality of the filtrate.The results of the experiments revealed that the reduction capacity of biological filtration processes for acetate is relatively high. Acetate removal resulted in an increased microbiological activity in the top layer (< 1cm) of the filter bed and accumulation of bacterial matter was observed at an influent AOC concentration as low as 0.005 mg of ac-C eq/l. Clogging of the filter bed occurred at an influent acetate concentration of 0.01 mg C/l. Based on these observations it was concluded that the AOC concentration of water used for infiltration in recharge wells should be less thon 0.01 mg ac-C eq/l. This level is similar to the level advised for biologically-stable drinking water.A linear relationship was found between the acetate removal in the experimental filters and the colony count in the filtrate. It was recommended that the AOC load in the final filtration process in water treatment therefore should be limited to prevent high colony counts in the filtrate, thus leading to the use of post disinfection.